Intra-Abdominal Hypertension and Abdominal Compartment Syndrome after Abdominal Wall Reconstruction: Quaternary Syndromes?. (June 2017) - Kirkpatrick, A. W.; Nickerson, D.; Roberts, D. J.; Rosen, M. J.; McBeth, P. B.; Petro, C. C.; Berrevoet, Frederik; Sugrue, M.; Xiao, Jimmy; Ball, C. G.
Background and Aims: Reconstruction with reconstitution of the container function of the abdominal compartment is increasingly being performed in patients with massive ventral hernia previously deemed inoperable. This situation places patients at great risk of severe intra-abdominal hypertension and abdominal compartment syndrome if organ failure ensues. Intra-abdominal hypertension and especially abdominal compartment syndrome may be devastating systemic complications with systematic and progressive organ failure and death. We thus reviewed the pathophysiology and reported clinical experiences with abnormalities of intra-abdominal pressure in the context of abdominal wall reconstruction. Material and Methods: Bibliographic databases (1950–2015), websites, textbooks, and the bibliographies of previously recovered articles for reports or data relating to intra-abdominal pressure, intra-abdominal hypertension, and the abdominal compartment syndrome in relation to ventral, incisional, or abdominal hernia repair or abdominal wall reconstruction. Results: Surgeons should thus consider and carefully measure intra-abdominal pressure and its resultant effects on respiratory parameters and function during abdominal wall reconstruction. The intra-abdominal pressure post-operatively will be a result of the new intra-peritoneal volume and the abdominal wall compliance. Strategies surgeons may utilize to ameliorate intra-abdominal pressure rise after abdominal wall reconstruction including temporizing paralysis of the musculature either temporarily or semi-permanently, pre-operative progressive pneumoperitoneum, permanently removing visceral contents, or surgically releasing the musculature to increase the abdominal container volume. In patients without complicating shock and inflammation, and in whom the abdominal wall anatomy has been so functionally adapted to maximize compliance, intra-abdominal hypertension may be transient and tolerable. Conclusions: Intra-abdominal hypertension/abdominal compartment syndrome in the specific setting of abdominal wall reconstruction without other complication may be considered as a quaternary situation considering the classification nomenclature of the Abdominal Compartment Society. Greater awareness of intra-abdominal pressure in abdominal wall reconstruction is required and ongoing study of these concerns is required.